Structural and optical characterization of tungsten phosphate glasses containing silver and erbium - Marcondes, L. M. [UNESP]; Santagneli, S. H. [UNESP]; Ribeiro, S. J.L. [UNESP]; Caiut, J. M.A.; Misoguti, L.; Nalin, M. [UNESP] (Elsevier, 2022)
Tungsten-phosphate glasses with up to 20 mol% of silver chloride content were prepared using the conventional melt-quenching method. Ag nanoparticles (AgNPs) formation was achieved by nucleation and growth using controlled thermal treatment. Thermal properties and the local structure were studied as a function of Ag content by means of DSC, Raman and 31P MAS NMR spectroscopy. The Ag NP growth was monitored by real-time UV–Vis spectroscopy and confirmed by TEM. The optical linear and nonlinear properties were evaluated as a function of the AgNPs growth. NIR emission of Er3+ ions was studied and showed a strong dependence on the AgNPs size. A weak luminescent enhancement occurs when small AgNPs are present, but on the other hand, a strong quenching takes place in the presence of larger AgNPs, due to the local field effect mediated by surface plasmon resonance (SPR) and Er3+ intersystem crossing processes, respectively. A stronger luminescence suppression by excitation at 545 nm was assigned to the increased contribution to back-energy transfer from Er3+ to AgNPs and re-absorption by SPR. These results highlight the importance of a careful study of the relation between noble metal NPs size and the excitation wavelength to increase the efficiency of the future photonic devices, such as NIR solid state laser, Kerr effect-based laser or amplifiers.
Keywords: Luminescence; Nonlinear properties; Phosphate glass; Silver nanoparticles; SPR band